ALUCONCRETE COMPOSITE BEAMS AND ARCHES - A. K. A., Razak; Roberts, T. M.; Bridle, R. J. (ASEAN JOURNAL ON SCIENCE AND TECHNOLOGY FOR DEVELOPMENT, 2005)
The results of an experimental investigation and theoretical study of aluconcrete composite beams is presented. Materials used to form the composite structure were a ready made extruded aluminium channel section beam and high strength con-crete (HSC) with a grade of 100 N/mm2. The basic properties of the materials were determined by conducting the following tests; i.e. tensile tests on aluminium; cube compression tests; tensile splitting tests; and cylinder torsion tests. The alucon-crete composite beams were subjected to four-point bending to assess their ultimate bending resistance. Based on the plastic behaviour of the materials used and cracked section analysis, a theoretical study was performed to assess the ultimate bend-ing resistance of the aluconcrete composite beams. Comparison between theoretical and experimental results was per-formed to validate the analysis. A good correlation was obtained between theoretical and experimental results. The applica-tion of the aluconcrete composite section to form the structural member (barrel) of the arch bridge was assessed. The results of the assessment show that the aluconcrete composite section could perform satisfactorily as the barrel of an arch bridge for loading of 80 kN per meter width.